Evaluation of Hair Cortisol in the Diagnosis of Hypercortisolism in Dogs. (19th July 2013) - Corradini, S.; Accorsi, P.A.; Boari, A.; Beghelli, V.; Mattioli, M.; Famigli‐Bergamini, P.; Fracassi, F.
Abstract : Background: Measurement of hair cortisol is a noninvasive technique used for several purposes in humans and in animals. Objectives: To measure hair cortisol concentrations (HCC) in dogs with spontaneous hypercortisolism (HC) and determine whether it can represent a useful diagnostic test for this syndrome. Animals: Twenty‐two dogs with spontaneous HC before treatment, 28 sick control dogs (SCD), and 40 healthy dogs. Methods: In this prospective, observational clinical study, the HCC was measured by an RIA assay after extraction in HC dogs, in dogs with other chronic diseases, and in healthy dogs. The diagnostic accuracy of HCC was evaluated by subjecting data from dogs with HC and dogs with other chronic diseases to receiver operating characteristic (ROC) curve analysis. Results: Median (range) cortisol concentration in dogs with HC was 4.53 pg/mg (0.32–74.62 pg/mg) and was significantly higher than in SCD (1.49 pg/mg, 0.13–14.19 pg/mg) and healthy dogs (1.28 pg/mg, 0.34–5.38 pg/mg). Within the 3 groups, there was a large overlap of HCC. The area under the ROC curve was 0.80 (95% CI: 0.67–0.92). A cut‐off value of HCC of 1.93 pg/mg revealed 91% sensitivity and 61% specificity to diagnose HC. Conclusions and Clinical Importance: Hair cortisol concentrations are higher in dogs with HC compared to SCD and healthy dogs. It is a noninvasive technique that should be further investigated as a possible diagnostic procedure for the diagnosis of HC in dogs.